Frequency of Placental Abruption in Patients with Pregnancy Induced Hypertension - Rasheed, Rubbia; Noor, Shehla; Romaesa; Umbreen, Sheeba (Indus Journal of Bioscience Research, 2025)
Background: Pregnancy-induced hypertension is a significant obstetric conditions that appears after the 20th week of pregnancy and is associated with various maternal and fetal complications. Placental abruption represent a serious complication characterized by premature separation of the placenta from the uterine wall before delivery. Objective: To determine the frequency of placental abruption in patients with pregnancy-induced hypertension. Study Design: Cross-sectional study. Duration and Place of Study: This study was conducted from January 2025 to May 2025 in the Department of Obstetrics and Gynecology, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 130 women aged 18 to 40 years with singleton pregnancy, gestational age more than 37 weeks and diagnosed with pregnancy-induced hypertension were included. Placental abruption was diagnosed based on clinical examination and ultrasound features. Data was analyzed using SPSS version 26. Chi-square test and Fisher exact test were applied for categorical variables. Results: The frequency of placental abruption was 13.10%. Significant associations were found with maternal age more than 30 years (p less than 0.001), gestational age more than 39 weeks (p less than 0.001), parity more than 3 (p less than 0.001), low socioeconomic status (p less than 0.001) and rural residence (p less than 0.001). Conclusion: Placental abruption is a considerable complication in pregnancy-induced hypertension with higher risk in advanced maternal age, increased gestational age and multiparity.